Antidiabetic Activity Test of Ethanol Extract of Bandotan Leaves (Ageratum conyzoides L.) in Alloxan-Induced White Rats - Puput, Puput Virgia Ningrum; Erida Novriani; Simanjuntak, Nerly Juli Pranita (CV. Nusantara Scientific Medical, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by elevated blood glucose levels, causing significant morbidity and mortality globally. Indonesia is one of the countries with the highest prevalence of diabetes. This study aimed to evaluate the antidiabetic activity of ethanol extract from Bandotan leaves (Ageratum conyzoides L.) in alloxan-induced diabetic white rats. This experimental research used 30 white rats divided into six groups: normal control (distilled water), negative control (distilled water+alloxan), positive control (glibenclamide 0.65 mg/kg BW+alloxan), and three groups receiving ethanol extract of Bandotan leaves (EEBL) at doses of 100, 200, and 400 mg/kg BW with alloxan induction. Extraction of Bandotan leaves was carried out using the maceration method using 96% ethanol, resulting in a yield of 37,35%. Phytochemical screening showed the extract contained alkaloids, steroids, quinones and saponins. Induction of diabetes was carried out by intraperitoneal injection of alloxan 30mg/kgBB. Blood sugar levels were measured on days 5, 10, 15, 20, 25, 30 after induction. The results showed that administration of EEDB significantly (p<0,005) reduced blood sugar levels with the best effect at a dose of 400mg/kgBB. The ethanol extract of bandotan leaves was proven to have effective antidiabetic activity in alloxan- induced mice, with the potential for development as an affordable and easily accessible alternative diabetes therapy.